2009
DOI: 10.1017/s0950268809991002
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and characterization ofStaphylococcus epidermidisisolates from humans, raw bovine milk and a dairy plant

Abstract: Geographically related Staphylococcus epidermidis isolates from human patients (n=30), dairy farms (farmers and individual raw milk from cattle, n=36) and a dairy plant (n=55) were examined for epidemiological relatedness by pulsed-field gel electrophoresis and, using in vitro methods, for the ability to produce biofilm and antimicrobial resistance. Methicillin-resistant isolates (MRSE) were also identified and characterized. Isolates from farmers and dairy cattle were found to be genetically related, while is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 41 publications
(68 reference statements)
3
29
0
Order By: Relevance
“…In addition, methicillin resistance does not seem to be widely spread among S. aureus isolates from bovine milk, which is in accordance with our results as well (Lim et al 2013;Unnerstad et al 2013). This is in contrast to S. epidermidis, in which methicillin resistance was commonly found (Jaglic et al 2010). However, similarly to the study of Overesch et al (2013), we observed a high prevalence (61.5%) of β-lactamase-producing (penicillin-resistant) isolates.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, methicillin resistance does not seem to be widely spread among S. aureus isolates from bovine milk, which is in accordance with our results as well (Lim et al 2013;Unnerstad et al 2013). This is in contrast to S. epidermidis, in which methicillin resistance was commonly found (Jaglic et al 2010). However, similarly to the study of Overesch et al (2013), we observed a high prevalence (61.5%) of β-lactamase-producing (penicillin-resistant) isolates.…”
Section: Discussionsupporting
confidence: 91%
“…S. aureus isolates were subjected to PFGE analysis as previously described (Jaglic et al 2010). The isolates were limited to one per sample except for five pairs of morphologically distinct isolates originating from five different samples.…”
Section: Methodsmentioning
confidence: 99%
“…The fact that raw milk is pasteurised prior to its processing indicates that other factors (e.g. personnel) may also play an important role in the contamination of the dairy plant environment (Jaglic et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Using PCR, the isolates were also examined for the presence of biofilm genes (icaAB and bap) as described previously (Cervinkova et al 2013). To confirm the persistence and clonality of S. aureus in the herd during the one year period, the isolates were subjected to pulsed field gel electrophoresis (PFGE) analysis as previously described (Jaglic et al 2010).…”
Section: Antimicrobial Susceptibility Biofilm Formation and Moleculamentioning
confidence: 99%